2020
DOI: 10.1002/smll.202004720
|View full text |Cite
|
Sign up to set email alerts
|

Selective Fabrication of Single‐Molecule Junctions by Interface Engineering

Abstract: Recent progress in addressing electrically driven single‐molecule behaviors has opened up a path toward the controllable fabrication of molecular devices. Herein, the selective fabrication of single‐molecule junctions is achieved by employing the external electric field. For molecular junctions with methylthio (–SMe), thioacetate (–SAc), amine (–NH2), and pyridyl (–PY), the evolution of their formation probabilities along with the electric field is extracted from the plateau analysis of individual single‐molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…261 Another innovative development is the use of an external electric field to influence junction formation probability in STM-BJ experiments. 262 It was found that OPEs with methylthio anchoring groups were increasingly likely to form junctions as the bias was increased, whereas thiol, amine and pyridyl anchors all showed reduced junction formation probability with increasing bias. This meant it was possible to demonstrate selective, preferential junction formation in a mixture of methylthioand thiol-anchored OPEs based on the applied electric field.…”
Section: Junction Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…261 Another innovative development is the use of an external electric field to influence junction formation probability in STM-BJ experiments. 262 It was found that OPEs with methylthio anchoring groups were increasingly likely to form junctions as the bias was increased, whereas thiol, amine and pyridyl anchors all showed reduced junction formation probability with increasing bias. This meant it was possible to demonstrate selective, preferential junction formation in a mixture of methylthioand thiol-anchored OPEs based on the applied electric field.…”
Section: Junction Materials and Methodsmentioning
confidence: 99%
“…This meant it was possible to demonstrate selective, preferential junction formation in a mixture of methylthioand thiol-anchored OPEs based on the applied electric field. 262 OAE derivatives are outstanding candidate molecules for developing novel molecular junction methodologies and as benchmark compounds for investigations of modifications to existing techniques. The ease with which structural modification can be achieved facilitates the translation of OAE wires to new electrode surfaces that require alternative anchoring groups.…”
Section: Junction Materials and Methodsmentioning
confidence: 99%
“…First, the strong electric field in the nanogap has an enrichment influence on molecular adsorption, so as to improve the local concentration and accelerate the reaction. [17] Second, the strong electric field, as generated by the applied bias, can further accelerate the reaction rate. [27] This finding also demonstrated the advantage of STM-BJ method, since it provides a safe and convenient method to study reaction under strong electric fields.…”
Section: Resultsmentioning
confidence: 99%
“…Single-molecule electronics have the potential to enable cheap and efficient circuit fabrication at the ultimate size limit and also provide an appealing test-bed for exploring intriguing physical phenomena at the nanoscale such as quantum interference, spin filtering, , and interfacial coupling. A significant and ongoing challenge in the investigation of transport through single-molecule systems, however, is extracting meaning from the large and stochastic data sets typically produced by experimental techniques such as the scanning tunneling microscope break junction (STM-BJ) and mechanically controlled break junction (MCBJ). Both of these methods involve forming and then breaking a thin metal constriction to create a single-molecule junction in the nanogap between two metal electrodes. The primary data collected is the conductance ( G = I / V ) through the junction during the breaking process as a function of how much the two sides have been pulled apart, known as a “breaking trace”.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of this so-called “molecular yield” varies depending on the binding group strength, molecular concentration, and other unknown or uncontrolled variables. , Figure uses simulated traces to illustrate that, for short molecules whose molecular plateaus mostly overlap with the tunneling background, low molecular yield can make the molecular signature functionally impossible to identify in both the 1D and 2D histograms. Partially for this reason, most break junction experiments focus on systems with molecular yields >10%, ,,,,, and often approaching 100%, ,, because this produces histograms with clear molecular features. However, high molecular yields increase the risk of measuring multi-molecule rather than the desired single-molecule features .…”
Section: Introductionmentioning
confidence: 99%